Morphological diversity and taxonomic implications of seedling structures in selected species of Fabaceae from Karachi (Pakistan) - Mahmood, Nabeela; Zaidi, Sahar; Riaz, Muniza; Omrani, Sumera; Sheikh, Anum; Qureshi, Huma; Anwar, Tauseef (Phytotaxa, 2024)
Seedling morphology is a valuable tool for plant identification and classification, particularly in early growth stages. This study investigates the morphological characters of seedlings from randomly selected taxa within the Fabaceae family, focusing on cotyledons, first two leaves, and subsequent leaves to support taxonomic differentiation. Not all subfamilies within Fabaceae are fully represented in this study. Seedlings from 14 randomly selected taxa were analyzed using morphological traits such as cotyledon shape, phyllotaxy, leaf shape, and venation patterns. An artificial key was constructed, and three dendrograms were developed based on cotyledon morphology, first two leaves, and subsequent leaves to illustrate taxonomic relationships. Statistical analyses were employed to assess clustering patterns among the taxa. The artificial key categorized the taxa into subfamilies within Fabaceae, including Caesalpinoideae, Mimosoideae, and Papilionoideae, based on cotyledon shape and leaf morphology. Dendrogram analysis revealed distinct clustering patterns, grouping species according to key morphological features. Not all subfamilies of Fabaceae were covered, but the analysis provided clear separation among the species studied. The morphological traits observed were consistent with previous taxonomic findings and offered a reliable basis for classification. The morphological features of seedlings, especially cotyledons and eophylls, serve as reliable taxonomic markers for identifying and classifying species within Fabaceae. Although the study does not encompass all subfamilies, the randomly selected taxa demonstrated clear taxonomic distinctions. Dendrograms combined with artificial keys provided a useful framework for classification. Further studies should expand the scope to include more taxa, covering all subfamilies of Fabaceae. Integrating molecular and other taxonomic tools such as anatomy, cytology, and chemistry can enhance the precision of classification frameworks and provide deeper insights into the evolutionary relationships within the family.